"She Looks Like Me": Putting High-Quality Multicultural Literature in Children's Hands During COVID-19. Issue 3 (27th May 2022) - Gunn, AnnMarie Alberton; Bennett, Susan V.; Peterson, Barbara J.
ABSTRACT: Amid the COVID-19 pandemic, children, families, and educators faced unprecedented challenges that disproportionally impacted racially/ethnically diverse, low-income communities due to long-standing health system, socioeconomic, and educational inequities. With closures of schools, libraries, and child-care centers, many children were disconnected from the community and did not have access to books. Parents' and educators' concerns centered around children falling behind academically and socially. Therefore, in partnership with an afterschool center, we purchased and distributed 410 high-quality, multicultural books to children and families. Case study design explored: (1) how this access to multicultural books influenced the CARC children's home-based literacy experiences and their responses to the texts; and (2) the challenges of parents/caregivers in supporting their child's literacy needs during a global crisis. We described how we selected high-quality multicultural literature book sets. We identified three themes: (1) enjoyment, appreciation, and learning; (2) relevance of multicultural literature to children's lives and identities; (3) difficulties during the COVID-19 pandemic. Through this collaboration, we increased access to multicultural books for children living in a low-socioeconomic and African American community. Our book distribution project positively impacted the children and families in this underserved community.